On the way to COVID-19 vaccine development: tireless efforts and outcomes - Pramanik, Tapas; Sur, Tapas Kumar (Journal of Physiological Society of Nepal, 2020)
Novel corona virus disease (COVID-19), since its emergence in November 2019, took the toll of a huge number of human lives. It is a β-corona-virus also known as SARS-CoV2. The safest and most effective way to prevent the disease is definitely vaccination amongst the large population. To the best of our knowledge, more than 200 vaccine candidates for COVID-19 were developed by the scientists of research institutions and pharmaceutical companies and nearly 52 candidates were in human trials. Till now, only 15 vaccines are being offered to the general population in the world, out of which 2 vaccines are RNA, 6 are conventional inactivated, 5 viral vector and 2 protein subunit. Here, we tried to unfold the events and efforts behind the successes of new innovations of COVID-19 vaccines, the world has achieved yet.